Rekacipta Antarmuka Pengguna Intuitif dan Ramah Pengguna untuk Sistem Operasi Windows: Pendekatan Berbasis Pengalaman Pengguna (Ux) - Rakhmadi Rahman; Abdul Khalik Hartono; Natasya taslim (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The rapid development of digital technology has led to the importance of intuitive and user-friendly operating systems. Windows, as one of the most widely used operating systems in the world, therefore we continue to strive to present a user interface (UI) that is not only functional but also easy to use. This journal discusses the project